Operator interpolation and systems of linear equations and inequalities in Euclidean spaces - Makarov, V. L.; Khlobystov, V. V.; Kashpur, O. F. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.988We obtain new criteria of compatibility for a linear system of equations (equivalent to the Kronecker - Capelli's theorem) and inequalities (equivalent to S. M. Chernikov's theorem), which are related to conditions for the existence of a linear interpolation polynomial in Euclidean spaces.